Treg‐cell depletion promotes chemokine production and accumulation of CXCR3+ conventional T cells in intestinal tumors. Issue 6 (14th April 2015) - Akeus, Paulina; Langenes, Veronica; Kristensen, Jonas; von Mentzer, Astrid; Sparwasser, Tim; Raghavan, Sukanya; Quiding‐Järbrink, Marianne
<x xml:space="preserve">Abstract</x> Colorectal cancer (CRC) is one of the most prevalent tumor types worldwide and tumor‐infiltrating T cells are crucial for anti‐tumor immunity. We previously demonstrated that Treg cells from CRC patients inhibit transendothelial migration of conventional T cells. However, it remains unclear if local Treg cells affect lymphocyte migration into colonic tumors. By breeding APCMin/+ mice with depletion of regulatory T cells mice, expressing the diphtheria toxin receptor under the control of the FoxP3 promoter, we were able to selectively deplete Treg cells in tumor‐bearing mice, and investigate the impact of these cells on the infiltration of conventional T cells into intestinal tumors. Short‐term Treg‐cell depletion led to a substantial increase in the frequencies of T cells in the tumors, attributed by both increased infiltration and proliferation of T cells in the Treg‐cell‐depleted tumors. We also demonstrate a selective increase of the chemokines CXCL9 and CXCL10 in Treg‐cell‐depleted tumors, which were accompanied by accumulation of CXCR3+ T cells, and increased IFN‐γ mRNA expression. In conclusion, Treg‐cell depletion increases the accumulation of conventional T cells in intestinal tumors, and targeting Treg cells could be a possible anti‐tumor immunotherapy, which not only affects T‐cell effector functions, but also their recruitment to tumors.